THE INFLUENCE OF ISLAMIC BRAND IMAGE AND SERVICE QUALITY ON TOURIST LOYALTY IN MUSLIM-FRIENDLY TOURISM DESTINATIONS: A STUDY OF THE AL-JABBAR GRAND MOSQUE TOURISM AREA, BANDUNG: (STUDI PADA KAWASAN WISATA MASJID RAYA AL-JABBAR BANDUNG) - Anggi Nurmalita (PT. Samudra Solusi Profesional, 2026)
This study addresses the growing need to understand tourist behavior in the rapidly expanding Muslim-friendly tourism sector, specifically focusing on the Kawasan Wisata Masjid Raya Al-Jabbar Bandung. While previous literature extensively reviews general service quality, there remains a critical gap in synthesizing how religious brand identity works simultaneously with tangible service elements to retain visitors. Grounded in contemporary consumer behavior theory, this research evaluates the impact of Islamic Brand Image and Service Quality on Tourist Loyalty. Utilizing a quantitative causal approach, data were gathered from 150 Muslim tourists through structured questionnaires and analyzed using multiple linear regression via SPSS. The empirical findings reveal that both Islamic brand image (t = 4.120, sig. = 0.000) and service quality (t = 6.845, sig. = 0.000) significantly and positively influence tourist loyalty, with service quality emerging as the more dominant predictor (β = 0.453). Simultaneously, both variables explain 53.2% of the variation in tourist loyalty (Adjusted R² = 0.532, F = 52.410). This paper demonstrates that a robust religious brand reputation must be backed by excellent operational standards to secure long-term loyalty. The value of this manuscript lies in its integration of spiritual and physical service dimensions, offering a strategic framework for destination managers to optimize their marketing strategies in competitive halal tourism markets.